Piles in weak rock (Thomas Telford for the Institution of Civil Engineers, 1977)
The purpose of this Symposium in print was to collect further data on the subject and to encourage future observation and publication of test pile results. These papers cover tests of bored and driven piles in Cretaceous mudstone at Port Elizabeth, South Africa, and the behaviour of bored piles in weathered diabase.